Pemberdayaan Masyarakat Kecamatan Pulomerak dalam Penurunan Stunting Melalui Posyandu Keliling - Putra, Arta Rusidarma; Dewi, Irma Nurmala; Triana, Leni; Afriani, Raden Irna (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The purpose of this community service activity is to increase the independence of all posyandu cadres in the Pulomerak District area in monitoring and monitoring toddlers who experience stunting and increase the knowledge of parents, especially mothers with toddlers who experience stunting problems. This community service is carried out by door-to-door method to the fifteen stunting toddler homes with cadres from each RW. The mobile posyandu activities using the door to door method went very well as seen from the high enthusiasm of the participants and the support from mothers of toddlers and cadres. The results of evaluating activities using the qualitative interview method show that in general the knowledge and treatment of parents, especially mothers, regarding stunting and the role of the posyandu is good.